An addendum to numerical modeling of an enhanced very early time electromagnetic (VETEM) prototype system. - Tie Jun Cui.
For original paper see Cui et al. (IEEE Antennas and Propagation Magazine, vol.42, no.2, p.17-27, 2000 April). Cui et al. proposed two numerical models to simulate an enhanced very early time electromagnetic (VETEM) prototype system, used for buried-object detection and environmental problems. In the first model, the transmitting and receiving loop antennas were accurately analyzed using the method of moments (MoM), and then conjugate gradient (CG) methods with the fast Fourier transform (FFT) were utilized to investigate the scattering from buried conducting plates. In the second model, two magnetic dipoles were used to replace the transmitter and receiver, because the working frequency for the VETEM system is usually low. Both the theory and formulation were correct, and the simulation results for the primary magnetic field and the reflected magnetic field were accurate. We have compared the simulation results for the magnetic field reflected by a wire-conductor mesh on the ground with measured data. They fit very well. However, the scattered magnetic fields in the simulation results were inaccurate, because we did not use a sufficient number of iterations in the CG-FFT algorithm when the frequency was very low.
Keywords: Numerical analysis; Electromagnetic scattering; Environmental problems; Buried object detection; Time domain; Loop antennas; Magnetic dipoles; Method of Moments